Comparative advantage as a success factor in football clubs: Evidence from the English Premier League (EPL) - Georgievski, B.; Labadze, L.; Aboelsoud, M. E. (Journal of Human Sport & Exercise, 2019)
As in international trade, football clubs can benefit more if they specialize in what they have or can create comparative advantage. In a world of scarce resources, clubs need to identify what makes them successful and invest accordingly. The main objective of this study is to understand what influences the success of football teams in the English Premier League (EPL) championship games. Based on Ricardo`s model of comparative advantage and applying Factor analysis as well as Panel data approach, this study investigates the need for specialization and tradeoffs between defensive and offensive patterns of the game in order for EPL clubs to be more successful. The data used in this study covers the period 2010-2017 of the EPL data. The results reveal that, in general, a better defense is slightly more important for success. The outcomes were different for the top- and bottom-ranking clubs. We found that it is more important for bottom-ranking teams to play better defensively than offensively, while for top-performing teams, the probability of success is more affected by offensive style. In addition, there is a tradeoff between these two styles of play; when bottom-ranking teams try to play better defensively, it often comes at the expense of a poor offensive pattern, but almost no one plays offense at the expense of a poor defense. Unlike the bottom-ranking teams, the top-ranking teams did not face tradeoffs, but they were able to improve both their defensive and offensive patterns. The recommendation put forward by this study argue that bottom-ranking clubs should specialize first in defense.